L'Objet Neutre - Franchi, Franca (Elephant & Castle, 2019)
In the Twentieth century, the sum of the literary explorations of the previous century inspired by the dream is the basis of a radical re-examination of the perceptual universe related to time, space, memory and emotions. Surrealism tries to mediate and assimilate the contradictory scope of this heritage through the conception of the neutral object. Expressions of the unconscious and receptacle of desire, objects are, by their nature, bisexual, androgynous, in short places of ambiguity. Our analysis, by questioning the vast surrealist repertoire of many objects used for functions keen to refer the expression of the unconscious and its instinctual equipment, focuses on the most encompassing: the city of Paris, in particular the Tower Eiffel, ambiguous erotic emblem and experience at the origin of the double sex of the gaze, of which Barthes will write in 1964.